Eco-Friendly Roller Compacted Concrete: A Review - Shahad Qais Abd Almajeed; Zena K. Abbas (Journal of Engineering, 2024)
Sustainable evolution is vital to address miscellaneous issues, and experts are currently exploring the possibilities of Eco-Friendly concrete (Green concrete). This type of concrete involves using environmentally and economically viable substances that can act as entire or partial replacements for conventional materials. By doing so, it can assist in reducing the consumption of natural resources and energy, as well as minimize pollution. For example, several researchers have performed on incorporating sustainable approaches in roller compacted concrete RCC by replacing certain substances with eco-friendly alternatives. That is a favorable step toward devising more sustainable construction practices. Therefore, this study resorted to reapplying recycled plastic garbage (sustainable plastic) to construct environmentally eco-friendly concrete (green concrete). First, examine the possibility of using plastic as a partial substitute for fine-aggregates in RCC mixtures. Second, examination of the possibility of using plastic as a partial substitute for coarse-aggregates in RCC mixtures to enhance the performance of RCC.  In early periods, a suitable RCC mix was designed in the lab to test the concrete strength, freezing-thawing, permeability, durability, erosion, and porosity of set concrete. The findings confirmed that RCC can maintain the same properties as traditional concrete using the known mixtures. Trial tests were designed and organized to evaluate the quality of pouring and compaction operations, suitable mix composition, and void specimens to accomplish testing on the constructed RCC.  It has shown that RCC with prime ingredients and proper ratios can be performed with similar strength and durability as conventional concrete. However, RCC differs from ordinary concrete pavements. This technology provides a favorable economical alternative for many branches of civil engineering installations.